Sistema de información web y el incremento de la eficiencia del proceso administrativo de la organización red empresarial del norte de Trujillo - Arias Capcha, Willy Angel (2018)
This research is titled “Sistema de Información Web y el incremento de la eficiencia del proceso administrativo de la organización Red Empresarial del Norte S.A.C. de Trujillo”. The main objective is to increase the efficiency of the administrative process of the aforementioned company, including registration and data requirements at any time in an agile, fast and effectively. With the implementation of the Information System Web it was achieved successfully performed using the RUP, plus programming languages used PHP and HTML for web and MySql content management database. The paradigm of Object Orientation continued, looking for an efficient and robust database model, following the principles of standardization and models concerning entity - relationship. The prospect of this work aims to contribute to the performance of the tasks performed in the company Business Network North and facilitate access to information staff and improve the efficiency of it.